2006
DOI: 10.2337/db06-0812
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Peripheral and Adipose Tissue Endocannabinoid System in Human Abdominal Obesity

Abstract: The endocannabinoid system has been suspected to contribute to the association of visceral fat accumulation with metabolic diseases. We determined whether circulating endocannabinoids are related to visceral adipose tissue mass in lean, subcutaneous obese, and visceral obese subjects (10 men and 10 women in each group). We further measured expression of the cannabinoid type 1 (CB 1 ) receptor and fatty acid amide hydrolase (FAAH) genes in paired samples of subcutaneous and visceral adipose tissue in all 60 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
437
10
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(506 citation statements)
references
References 43 publications
41
437
10
18
Order By: Relevance
“…58 Furthermore, circulating 2-AG was significantly correlated with body fat, visceral fat mass, and fasting plasma insulin concentrations, but negatively correlated with glucose infusion rate during clamp in a group of ten men and ten women. 59 Obese subjects had a reduction in adipose tissue FAAH gene expression compared with lean individuals 58,59 , and FAAH gene expression was negatively correlated with visceral fat mass and with circulating 2-AG. 59 Another group also showed higher levels of 2-AG in the serum and visceral, but not subcutaneous, fat of obese subjects.…”
Section: Human Datamentioning
confidence: 95%
See 1 more Smart Citation
“…58 Furthermore, circulating 2-AG was significantly correlated with body fat, visceral fat mass, and fasting plasma insulin concentrations, but negatively correlated with glucose infusion rate during clamp in a group of ten men and ten women. 59 Obese subjects had a reduction in adipose tissue FAAH gene expression compared with lean individuals 58,59 , and FAAH gene expression was negatively correlated with visceral fat mass and with circulating 2-AG. 59 Another group also showed higher levels of 2-AG in the serum and visceral, but not subcutaneous, fat of obese subjects.…”
Section: Human Datamentioning
confidence: 95%
“…59 Obese subjects had a reduction in adipose tissue FAAH gene expression compared with lean individuals 58,59 , and FAAH gene expression was negatively correlated with visceral fat mass and with circulating 2-AG. 59 Another group also showed higher levels of 2-AG in the serum and visceral, but not subcutaneous, fat of obese subjects. In a further study in untreated asymptomatic men, plasma 2-AG levels correlated positively with body mass index (BMI), waist girth, intra-abdominal adiposity, fasting triglycerides and insulin levels, and correlated negatively with HDL-C and adiponectin levels.…”
Section: Human Datamentioning
confidence: 95%
“…Therefore, it is not known if interventioninduced changes in EC levels correlate with changes in metabolic dysfunctions associated with VAT. Such an observation would establish a relationship between the overactive endocannabinoid system and some metabolic risk factors that is stronger than that implied by crosssectional studies [3,4]. In the present study, we aimed to obtain this information by investigating, in a sample of viscerally obese patients, the effect of a 1 year lifestyle modification programme, consisting of healthy eating and regular physical activity/exercise, on EC levels, VAT accumulation and metabolic cardiovascular risk factors.…”
mentioning
confidence: 94%
“…In obese patients, higher levels of the EC, 2-arachidonoylglycerol (2-AG), but not of another EC, anandamide, are found in VAT, but not subcutaneous adipose tissue (SAT), as compared with lean volunteers [2]. In two independent cross-sectional studies, increased plasma levels of 2-AG, but not anandamide, were shown to correlate with high levels of VAT, but not SAT, as well as with several of the aforementioned metabolic alterations [3,4]. In view of the proposed pro-lipogenic and glucose intolerance-inducing actions of CB 1 receptor stimulation in rodents [1], an upregulated EC system in the VAT of obese patients might lead to an increased VAT accumulation and contribute to ectopic fat accumulation and insulin resistance.…”
mentioning
confidence: 99%
“…For example, genetic and diet‐induced obese animal models display elevated endocannabinoid levels in the hypothalamus and peripheral tissues (Di Marzo et al ., 2001; Osei‐Hyiaman et al ., 2005; Matias et al ., 2006). Furthermore, increased circulating levels of AEA and 2‐AG, as well as elevated levels of 2‐AG within visceral adipose tissue, have been reported in obese and/or hyperglycaemic type 2 diabetic patients (Bluher et al ., 2006; Matias et al ., 2006). In accord with this, hyperactivation of CB1R‐induced signalling has been implicated in numerous metabolic abnormalities including hyperphagia, insulin resistance, glucose intolerance and impaired lipid homeostasis (Engeli et al ., 2005; Jbilo et al ., 2005; Osei‐Hyiaman et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%